Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 623875312 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "Country is Holy See", "Country is Monaco", "Country is San Marino", "Country is Liechtenstein", "Country is Malta", "Country is Andorra", "Country is Georgia", "Country is Luxembourg", "Country is Cyprus", "Country is Azerbaijan", "Country is Kosovo", "Country is Montenegro", "Country is Slovenia", "Country is Turkey", "Country is North Macedonia", "Country is Albania", "Country is Armenia", "Country is Belgium", "Country is Moldova, Republic of", "Country is Netherlands", "Country is Switzerland", "Country is Denmark", "Country is Estonia", "Country is Slovakia", "Country is Bosnia and Herzegovina", "Country is Croatia", "Country is Latvia", "Country is Lithuania", "Country is Ireland", "Country is Serbia", "Country is Czechia", "Country is Austria", "Country is Portugal", "Country is Hungary", "Country is Iceland", "Country is Bulgaria", "Country is Greece", "Country is Belarus", "Country is Italy", "Country is Poland", "Country is Finland", "Country is Germany", "Country is Romania", "Country is United Kingdom of Great Britain and Northern Ireland", "Country is Norway", "Country is Sweden", "Country is Spain", "Country is France", "Country is Ukraine", "Country is French Guiana", "Country is Guadeloupe", "Country is Martinique", "Country is Saint Martin (French part)", "Country is Mayotte", "Country is Réunion", "Country is Greenland", "Country is Curaçao", "Country is Aruba", "Country is Sint Maarten (Dutch part)", "Country is Bonaire, Sint Eustatius and Saba", "Country is French Polynesia", "Country is New Caledonia", "Country is Wallis and Futuna", "Country is Saint Barthélemy", "Country is Saint Pierre and Miquelon", "Country is French Southern Territories", "Country is Faroe Islands", "Country is Anguilla", "Country is Bermuda", "Country is British Indian Ocean Territory", "Country is Virgin Islands (British)", "Country is Cayman Islands", "Country is Falkland Islands (Malvinas)", "Country is Gibraltar", "Country is Montserrat", "Country is Pitcairn", "Country is Saint Helena, Ascension and Tristan da Cunha", "Country is South Georgia and the South Sandwich Islands", "Country is Turks and Caicos Islands" ] }, "OccurrenceStatus is Present" ] } The dataset includes 623875312 records from 12357 constituent datasets: 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 1 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1916 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 79238 records from Inventaire de la flore de Dordogne 2017. 3572 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 4697245 records from Observations du Conservatoire botanique national du Bassin parisien.. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 808 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 1 records from MZFC/Coleccion de Aves. 847 records from TNHC Herpetology Collection. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 4422 records from Macaulay Library Audio and Video Collection. 3882 records from Museu Darder de Banyoles. 30 records from Occurrence of mammalia relicts at site Kugelsteinhöhle II. 722 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 185 records from DMNS Egg Collection (Arctos). 996 records from Geochemistry and sedimentology on core POS200/10_6-2. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1218925 records from Vascular Plants, Field notes, Oslo (O). 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1009 records from Study on plankton at the port of Ostend in 1965. 1321 records from Priest Pot species list, Cumbria, Britain. 31 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 131 records from Orthoptera - SMF. 5783 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 3 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 214 records from University of Michigan Museum of Paleontology - Vertebrates. 4174 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 1 records from Morphological and molecular analyses support the amphi-Atlantic distribution and taxonomic status of the snapping shrimp Alpheus intrinsecus Spence Bate, 1888 (Crustacea: Decapoda: Alpheidae). 1937 records from Données naturalistes d'Océane ROQUINARC'H. 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 45991 records from Herbarium Universitatis Daugavpiliensis. 32738 records from SANT-Algae. 2 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 1 records from Colección de Entomología - Curculionidae. 1 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 3 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 34 records from National System of Protected Areas in Poland - Fungi. 64 records from Pilzlehrwald. 765465 records from International Barcode of Life project (iBOL). 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 601 records from LBV 100 - Artenvielfalt am Rothsee. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 182 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 144 records from Données naturalistes de Xavier BONNET. 2 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 971 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 330043 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 4 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 6223 records from Plecoptera. 44 records from Flora und Fauna in unserer Kita. 1015 records from Programme ACT : Répartition Merle noir 2005 - 2009 Coordonnées GPS Lambert 93. 33 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 15320 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 3 records from Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean. 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 114 records from Flora. 6 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 1 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 84 records from BIRDRACE Avinauten. 1 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 1 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 650 records from Données 2016 de la Ligue de Protection des Oiseaux de Touraine. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 2445 records from Flore des Pyrénées. 76124 records from Lichen field notes, Oslo (O). 20367 records from Collection Mollusca SMF. 14 records from Collection Amphibia fossil SMF. 61674 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 150 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 8862 records from Données naturalistes de Benoit MARTHA. 121778 records from Observations occasionnelles Parc national des Pyrénées. 120 records from BIRDRACE The early birds. 2 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 69 records from Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 18 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 87 records from Foraminifera abundance of sediment core IN68-21. 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 1456 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 10149 records from Bumblebees, cuckoobees and butterflies in southern Poland. 6979 records from Upper Silesian Museum, Bird Observations. 1 records from ISM Ichthyology Collection. 515 records from DREAL Auvergne - Amphibiens - 2015. 1182 records from Données naturalistes de Quentin ROME. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 269 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 749 records from Carabidae of Wales and England. 30 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 131 records from Artenvielfalt auf dem Schulgelände. 497 records from Données Opération escargots. 17171 records from North Sea plastic incubation and reference communities, raw sequence reads. 2 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 7876 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 21 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 36 records from Triticale French National Collection. 5426 records from Collection Francaise de Bacteries Phytopathogenes. 484 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 136 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 133 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 188 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Données de la naturaliste Laurence Beauchamp. 91 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 2278 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 126 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1708 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 98 records from Living Cirripedia. 1 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 1284 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 914 records from Naturhistorisches Museum Mainz, Botanical Collection. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 2 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 222 records from Land and freshwater molluscs of Northern Spain. 4 records from Hormigas (Hymenoptera: Formicidae) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 4 records from Microplankton abundance at bottle station SEPT-1999-K2. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 22616 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Department of Plant Protection. 28 records from University of Nebraska State Museum Birds Collection. 1793 records from Herbarium BSG Lichenes. 7 records from University of California Santa Barbara Invertebrate Zoology Collection. 3 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 21 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 7561 records from Données chiroptères. 64 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 627 records from Etude des coléoptères de l'ENS de Voulangis (77). 2 records from Neue Milbenarten aus Kärnten. 7228 records from Grand_Site_Sainte-Victoire_2017_12_18. 10 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 876 records from MfN - Fossil vertebrates V. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 229 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1158 records from Entomology Collection at the Natural History Museum of Utah. 2 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 2 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 95 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 166 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 2264 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 781 records from Herbarium specimens of Limoges university (LIMO). 1 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 4478 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 577 records from Fish specimens of Kagoshima University Museum. 1 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 49 records from UTEP Invertebrates (Arctos). 3321 records from Diptera Collection of Museum and Institute of Zoology PAS. 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 7 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 2 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 59 records from Schulteich Freie Waldorfschule Darmstadt. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 18 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 1 records from MEXU/Leguminosae. 6451 records from DBRC Arvicola amphibius records 1925 - 2016. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 1136 records from Spider Mites Collection of Jean Gutierrez. 35 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 26 records from Schulteich Heinrich-Mann-Schule. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 435 records from Collection botanique Mulon L. (BOUM). 36 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 165 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 371 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 649 records from R. L. McGregor Herbarium Vascular Plants Collection. 25473 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 60311 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 9 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 13 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 2 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1 records from COA Bird Collection (Arctos). 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 28 records from University of Guam Insect Collection. 90 records from Invasive species - Ruddy duck (Oxyura jamaicensis) in Flanders, Belgium. 3 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 28 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 5420 records from Données des membres de l'Association française d'Arachnologie. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2454 records from Amphibian and reptile data for Dumfries and Galloway.. 2307 records from Museu de Ciències Naturals de Barcelona: BGJBB. 22187 records from OPIE_National_2017_12_18. 3 records from New cave-dwelling Plakina (Plakinidae, Homoscleromorpha, Porifera) from Martinique Island (French Antilles). 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 204 records from Survey of Eurasian otter distribution in the Glenmore - Aviemore area, 2018: Camera trap mammal records. 8348 records from CAS Herpetology (HERP). 5002 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 48 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 2 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 7214 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 4374 records from French Grapevine Genetic Resources Center. 306 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 789 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 2398 records from Collections of Bioclass, school #179, Moscow. 580 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 35461499 records from EOD - eBird Observation Dataset. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 58457 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification certaine. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 158 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 10 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from UWIZM Anoles. 5 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 1017 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 2 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 1109 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 148 records from Überall ist Wunderland. 16959 records from INNS Data: All Taxa (West Wales). 10 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 4249 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 15 records from Counts (1) of calcareous dinocysts along profile Stevns-Klint. 220 records from Données naturalistes de Ingénieurs écologues GEREA. 2 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 2 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 449 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 196 records from Données naturalistes de Marie-France LECCIA. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 1633 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 43 records from Nannofossil abundance of Hole 49-409. 3 records from Herbier Louis-Marie (QFA) - Collection de lichens. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 160700 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 2 records from USGS Alaska Science Center Polar Bear Maternal Dens. 1709 records from suspended particulate matter Raw sequence reads. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 73 records from Planktic foraminifera abundance of Hole 49-409. 192 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 119 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 51 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 2 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 1328 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 4 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 37328 records from AMNH Bird Collection. 915 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 2756 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des données Odonates. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 2134 records from Kurzflügler_Raw1. 5 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 5 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 4 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 13235 records from RECORD Bryopsida Data. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 330 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 2099 records from BioBlitz Barcelona 2010-14. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Art´n Vielfalt im Kinderwald. 5 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 461 records from Invasive Non-Native Species, Outer Hebrides. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 1 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 7213 records from hymenoptera. 1110 records from FFH-Gebiet "Calwer Heckengäu". 27894 records from Naturalis Biodiversity Center (NL) - Crustacea. 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 12147 records from Danish Ants (Formicidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 23 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 34 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 81532 records from Bob Merritt Coleoptera Dataset. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 14141 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 1 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 1045440 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 237179 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 2 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 109 records from Projet Diable de mer - AILERONS. 14 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 1251 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 28 records from The Broward College Insect Collection. 3166 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 2 records from Données naturalistes de LEMOIGNE JONATHAN. 70 records from Berea College, Ralph L. Thompson Herbarium. 1012 records from Programme ACT : Répartition Merle noir 2011 - 2015 Coordonnées GPS Lambert 93. 2 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 103 records from Schwanseepark (87645 Schwangau). 1 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 1 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 9657 records from Ecosphère_2017_12_18. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 3 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 70781 records from Birds ringed with Norwegian rings 1914-1960. 114 records from BIRDRACE VIE will rock you!. 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 78 records from Données de la naturaliste Anna Even. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 3 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 13671 records from Données du naturaliste Julien Birard provenant de la base de donnée du SINP Île-de-France CETTIA. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 596 records from Range table from benthic foraminifers in ODP Hole 149-900A. 117 records from Streuobstwiese Stedar 2009. 95 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 3514 records from CM Vertebrate Paleontology Collection. 101 records from UCLA Donald R. Dickey Bird and Mammal Collection. 8 records from Die Bachspezies 2008/2009. 45139 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 843 records from University of Vermont, Pringle Herbarium, Algae Collection. 17 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 68 records from Streuobstwiese. 10551 records from Données LPO Réserve naturelle régionale du marais de la Vacherie. 4951 records from SIM-Fungal records compiled by Joan Montón. 1526 records from Western Australian Museum provider for OZCAM. 19619 records from Carabidae of the Carpathians. 2591 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 2778666 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 272770 records from NRW Regional Data: South East Wales Non-sensitive species. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 6921 records from Xylophaga in situ Eclusion Experiment. 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 30 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 33393 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 35 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 642 records from Protistan plankton diversity along salt gradient. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31508 records from Polish gene bank – passport data of plants accessions which are important in human life. 5 records from Occurrence of mammalia relicts at site Rotselaar. 10 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 45984 records from Naturalis Biodiversity Center (NL) - Diptera. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 75 records from Données du naturaliste Matthieu Gouirand. 85 records from Birdrace-Die_Paradiesvögel-Herford. 174 records from BIRDRACE Bon(n)apartemöwen. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 2393 records from SANT-Bryo. 84 records from Plathelminthes - SMF. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 101 records from Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 5 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 334 records from Amphibia Collection of Museum and Institute of Zoology PAS. 61 records from Cowan Tetrapod Collection - Mammals. 24 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 4 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 550 records from Pollen and spore abundance of Hole 42-380A. 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 3 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 1 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 13709 records from Données naturalistes de Bruno OGER. 1444 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 16 records from Données naturalistes de ROLLAND Blandine. 6202 records from Lichens of North-Eastern Poland. 82 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 52 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 6192 records from NE Scotland fish records 1800-2010. 2749 records from artsprosjektet_53-12_enchytraeidae. 6 records from Anmerkungen zur Gattung Dapsa L, 1829 (Coleoptera, Endomychidae). 1 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 363415 records from Paleobiology Database. 39 records from Marine sediment metagenome ICM_GMS. 37 records from Entocytheridae (Ostracoda) World Database. 9 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 996 records from Pollen profile ADR353. 57919 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 102 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 15 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5676 records from SNH Bat Casework records 1970-2007. 1 records from Two new species and ten new records of Heteroptera from Turkey, including the first record of the potential alien Campylomma miyamotoi in the Western Palaearctic. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 8 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 5 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 825 records from Pollen profile ADR309. 8 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 464 records from Données espèces - Expertise IQE 306. 1737 records from Données Nature 18 - Études faune 2016. 3502 records from University of Minnesota Insect Collection. 290976 records from ARABEL - Arachnologia Belgica. 133564 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 2872 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 6993 records from Arctic Species Trend Index (ASTI) : Marine. 5202 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 2706 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 377 records from LSUMZ (LSU MNS) Fishes Collection. 33 records from MLZ Bird Collection (Arctos). 15 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 6 records from 2. Donauinsel bei Entau. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 3 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 1 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 85 records from Gastropod Specimens of the Yamagata Prefectural Museum. 1177 records from Ornithologie Federsammlung - SNSD. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 2 records from Perotrochus caledonicus (Gastropoda: Pleurotomariidae) revisited: descriptions of new species from the South-West Pacific. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 3541 records from LISU Lichen collection. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 1 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 46 records from Liether Park (LMS), 5a. 2314 records from Midden-Limburg Fish Ponds Survey. 92061 records from Herbarium (ICEL). 51048 records from Herbarium Senckenbergianum (FR) - Fungi. 6478 records from National System of Protected Areas in Poland - Animals. 12280 records from Leiner-Herbar Konstanz. 1 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 898 records from Kyklades-data of the Central Aegean Sea. 16048 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 895 records from Geometridae de France métropolitaine. 1 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 204 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4193 records from Leicestershire and Rutland Aculeate Records. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16618 records from Suivi Temporel des Libellules (STELI). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 106 records from Sylter Meerstrandläufer. 125 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 5 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 57 records from Reptilia ZMK. 32534 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1380 records from Plant observations from Białowieża National Park. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 1290 records from Diversity of Spiders from Azorean Trails. 70 records from Ensemble des données Orthoptères. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 648 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 2012 records from Pollen profile RAC20, Lake Racou, France. 225 records from Tillegg Røtinga i Os. 28 records from Données naturalistes de Franck MERLIER. 110 records from US herbarium - Smithsonian Institute - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 899 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 2808 records from Natura 2000 Vallée de la Seille. 2 records from UAM Herbarium (ALA), Algae Collection (Arctos). 211 records from Etude naturaliste des landes et pelouses à Fulchiron, Maisse (91). 989 records from Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 21 records from (Table 3) Foraminiferal census data and derived sea surface temperatures in sediment core JM01-1199, southern Barents Sea. 18417 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 46 records from Planktic foraminifera abundance of Hole 9-76. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 2579 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 14466 records from Jeu de données de la Société limousine d'Etude des Mollusques. 1201 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 286 records from schulgarten. 102374 records from Données de Mammifères collectées par le Groupe Mammalogique d’Auvergne et la Ligue pour la Protection des Oiseaux Auvergne.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 21 records from Tauchen und Meer 02. 13 records from Données naturalistes de THÉVENOT Jessica. 2 records from Sediment properties of core CD86_09_PC. 27 records from Occurrence of mammalia relicts at site Biedermann. 35084 records from Inventaire de la flore de Lot-et-Garonne 2017. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 29 records from Lucanidae. 16 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 7855 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 102 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 37102 records from TWIC Biodiversity Field Trip Data (1995-present). 101 records from Données naturalistes de LE GLOANEC Vincent. 136 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 386 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 227 records from MSUM Ichthyology and Herpetology Collections. 7 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 18 records from Genebank, National Institute of Agrobiological Sciences. 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 41 records from Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 1 records from Myolaimus ibericus sp. n. (Nematoda, Rhabditida, Myolaimidae) from southern Iberian Peninsula, with a key to species of the genus. 31361 records from River Biologists' Database (EPA). 194040 records from Tiroler Landesmuseum Ferdinandeum. 2324 records from Eriophyoid Mites of Poland. 794 records from Isle of Wight non-native invasive species. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 2822 records from Synthèse de la répartition des populations de cerf élaphe en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 17 records from Marine metagenome ICM_AGW. 17 records from Weber State University Herbarium. 117904 records from Biological Impacts of Ocean Acidification. 105 records from STERF 2014/2015 Hasparren (64) par l'association EcoGIS. 106 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 758 records from Programme ACT : Répartition Grive draine 2004 - 2008 Coordonnées GPS Lambert 93. 9716 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 169587 records from National Mammal Atlas Project, online recording. 1227 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 53 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 417 records from Benthic foraminifera counts of sediment core GIK23351-1. 8851 records from Odonata records from RSPB Reserves 1970-2009. 858 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 756 records from (Table 4) New palynological record of sediments from Odderade. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 7270 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 1709627 records from NBIS Records to December 2016. 118 records from Nezara viridula records held by the Royal Horticultural Society. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 3481 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 7 records from California State University, Long Beach Birds. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey. 6 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 18 records from Collection Hydrozoa - ZSM München. 358 records from Marine metagenome ICM_AWP. 33 records from Occurrence of mammalia relicts at site Sveduv stul. 40780 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 121 records from Foraminifera abundance of sediment core IN68-28. 5 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9056 records from NE Scotland other invertebrate records 1800-2010. 1267 records from SEWBReC Fish (South East Wales). 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 61 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 23831 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 281 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 74729 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 26 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 16844 records from Données Entomologiques A. HORELLOU 1988-2018. 77 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 5910 records from Benthic foraminifera abundance in per cent of Hole PRAD1-2. 30 records from Geführte Wanderung im Eselsbachtal. 1895 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 225 records from Records of Halicarcinus planatus at sub-Antarctic regions. 20 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 2177 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 104 records from Urwald 1 (Bad Waldsee). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 122 records from Birdrace-Hügelland-Mainz/Bingen. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 391 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/18. 111 records from Ichthyologie ZMK. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 37 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 48402 records from Insects, Outer Hebrides. 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 1 records from Description of eight new species of the traumatically inseminating plant bug genus Coridromius (Heteroptera: Miridae: Orthotylinae: Coridromini). 220 records from Mammals in MZNA-VERT: project Loza. 22 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 185 records from Inventaire des odonates d'intérêt communautaire. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 2116 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 5 records from BioGIS - Vascular plants - Israeli Gene Bank. 1 records from Insect (KIDR-IN). 1014 records from Programme ACT : Répartition Merle noir 2009 - 2013 Coordonnées GPS Lambert 93. 1 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 15 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 9 records from Sea Education Association Sargasso Sea Cruise C247 May 2013. 1634 records from Invertebrates (except insects), Outer Hebrides. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 77 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 1723 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 1 records from Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran. 3 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 62 records from Sibojaï_2017_12_18. 259 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 151 records from Meetnetten.be - Fyke counts for Amphibia in Flanders, Belgium. 277 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 1174 records from DBRC Lutra lutra records 1952 - 2016. 39 records from New records for Albania based on taxa from the Prespa National Park. 3 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 37479 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 6 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 1633 records from Diatom abundance of Hole 38-338, Part 2. 103 records from Distribution of planktonic foraminifera of sediment core SH1972_10. 1382 records from Observations opportunistes de mammifères marins de l'observatoire PELAGIS. 7 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 333 records from Langes Tannen (Uetersen). 2756 records from Marine Turtles. 2247 records from Churchyards for London. 258 records from Etude d'impact projet cluster des médias Jeux Olympiques. 8 records from Aktion des Romain-Rolland-Gymnasiums. 1 records from Conringia orientalis. 3 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 41322 records from Inventaire de la flore de Lot-et-Garonne 2016. 783 records from Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 7299 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 67 records from Données du naturaliste JOB Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 463 records from Foraminifera abundance of sediment core IN68-9. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 9 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 9668 records from Guadeloupe_Herbier. 1 records from Données naturalistes de Caroline DAGNEAU. 1 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 13 records from Range table from ostracoda in ODP Hole 160-967A. 123 records from City of Edinburgh Natural Heritage Service - Hillend Wildflower Meadow Survey. 1 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 101 records from Naturgrundstück (Eutin). 135 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 229 records from données araneologiques de LEENKNEGT Virginie. 22 records from Herbarium Senckenbergianum (FR) - Protista. 1 records from Colección de helechos de la FML. 3 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 8 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 2310 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 1 records from Zoology in the Middle East. 111 records from Données naturalistes de Mr MONTAGNER Sylvain. 213 records from Occurrences of Spalax zemni. 68916 records from Données de l'Observatoire de la Faune de Bourgogne. 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 16 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 10 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 12 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 11 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 8 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1164 records from Données du partenariat Imerys - UMS PatriNat - 2018-2020. 5410 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 1 records from Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 2 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 9 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 117 records from Nannofossil abundance of Hole 49-408. 15 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 6659 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 18135 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 3 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 26 records from Schwedische Oribatei (Acari). III.. 221 records from Mission ONF 2008 d'inventaire de la Réserve naturelle de la Trinité. 92 records from Birkenloh. 788 records from Species observations during citizen science expeditions. 188215 records from inatura - Erlebnis Naturschau Dornbirn. 18 records from CAS Entomology Type (TYPE). 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 9 records from Sponges of the Guyana Shelf. 119 records from Kinorhyncha. 2984 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 1618 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 615 records from Marine subseafloor sediment Targeted Locus (Loci). 10 records from Notes on the genus Echinops L. (Asteraceae) in SE Europe. 11 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 63 records from CHAS Ornithology (Arctos). 7125 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 10 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 58 records from Ostracoda abundance of Hole 42-372. 10 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 3579 records from Amphibian and reptile records for Great Britain 2016-2019. 385 records from (Appendix 3) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD99-2341. 6 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 23648 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 92 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 482 records from Kühmark bei Wetzlar. 192 records from "Ahrschleife bei Altenahr". 2574 records from South Australian Museum Australia provider for OZCAM. 126 records from Regionalpark(Hattersheim). 131 records from Foraminifera abundance of sediment core BM1958.631. 108 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 148 records from Herbarium BSG Hepaticopsida. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 9 records from Brock University Herbarium (BU). 411 records from Planktic foraminifera distribution of sediment core CS72-37. 23 records from Mains of Kinblethmont Solar Park Amphibian Records 2014. 3 records from Review of the genus Saropogon Loew, 1847 (Diptera: Asilidae) from Russia Transcaucasia and Central Asia, with description of three new species. 117 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 38 records from Données naturalistes de Cédric POUCHARD. 69 records from Unter hellen Zinnen und finsteren Grotten. 273 records from Données espèces - Expertise IQE 119. 13 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Feathers_and_Skin. 888 records from Inventaire des Rhopalocères. 17 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 23 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 72 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 12 records from Occurrence of mammalia relicts at site Niederlehme. 102 records from Swedish Malaise Trap Project (SMTP) - Evaniidae. 1264 records from Grand Voyeux - Suivis scientifiques. 2366 records from Cryoconite sediments Targeted Locus (Loci). 1 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 31223 records from DIPOL. 37342 records from Inventaire de la flore des Landes 2017. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 460 records from EDIT - ATBI in Gemer area (Slovakia). 420 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 10758 records from données aranéologiques de LEDOUX Jean-Claude. 88 records from Teich Berlin Wuhlheide. 26 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 417 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 152 records from AKG-Gelände (Bensheim). 471 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Occurrence of mammalia relicts at site Raagelund. 160 records from Données espèces - Expertise IPE 37. 2 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 154 records from Shannon Index and species richness for arthropods. 57920 records from Online Atlas of Vascular Plants 2012-2020. 10696 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 8 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 1210 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from Revision of Scelio pulchripennis - group species (Hymenoptera, Platygastroidea, Platygastridae). 396 records from Crustacea ZMK. 1 records from Revisão Do Gênero Runibia (Heteroptera, Pentatomidae, Pentatomini). 2 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 210 records from Lebensraum Gesamtschule (Langerwehe). 4798 records from ICEL (Land - Invertebrates). 246 records from UTEP Herpetology (Arctos). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 29 records from A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy. 8271 records from Biological Reference Collections ICM-CSIC. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 2497 records from Données des collections d'algues du MNHN. 5346 records from AMNH Herpetology Collections. 73 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 939 records from Coléoptères Silphidés du département du Loiret. 1 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 137 records from Lynx 2011 présence Occasionnelle Maille 10km Réseau Loup-Lynx ONCFS. 4 records from CNAN/Pseudoscorpiones. 6869 records from MfN - Fossil invertebrates IIb. 1375 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 192 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1817 records from Données de la structure Fédération 77 de Pêche et Protection du Milieu aquatique provenant de la base de donnée du SINP Île-de-France CETTIA. 79 records from UAM Invertebrate Collection (Arctos). 123 records from Occurrence of mammalia relicts at site Veternica. 4 records from The genera and species of Comatulidae (Comatulida: Crinoidea): taxonomic revisions and a molecular and morphological guide. 2 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 2 records from Benthic foraminifera abundance of Hole 42-376. 73 records from Données du/de la naturaliste Livet Bertrand provenant de la base de donnée du SINP Île-de-France CETTIA. 348 records from SNH Invertebrate Site Condition Monitoring 2013/14: Black Wood of Rannoch SSSI. 6 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 53 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 10 records from Colección Ictiológica del CENPAT-CONICET. 26 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 90 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island. 56061 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 144 records from artsprosjektet_45-15_helvella. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 6 records from Données naturalistes de Noé Conservation. 53 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 58 records from Golf de Chantilly. 2558 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Tromsø. 4 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 436 records from Automatic acoustic Monitoring and Inventoring of BIODiversity. 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 516 records from Nannofossil abundance of Hole 15-149. 64 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 3084 records from Herpetile collection NTNU University Museum. 16 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 113 records from Size of planktic foraminifera at CTD station PS55/084-1. 1861 records from Données du naturaliste DELAPRE Jean-Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 19 records from Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae). 140 records from Swedish Malaise Trap Project (SMTP) - Braconidae: Cheloninae: Adelius. 390 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE272. 2751 records from Tidal and diurnal rhythms of the hyperbenthos at the 'Vlakte van de Raan' on 14 October 1996. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 38 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 64 records from First catalogue of the Asopinae (Hemiptera, Pentatomidae) from French Guiana. 9 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 5 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 3 records from Colección de Rosales, Salviniales, Santalales, Sapindales, Saxifragales, Schizaeales y Selaginellales del Museo Botánico CORD - IMBIV. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 345 records from Meetnetten.be - Site counts for butterflies in Flanders, Belgium. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 39 records from Swedish Malaise Trap Project (SMTP) - Formicidae. 373 records from Otter survey of Ireland 2004 & 2005. 795 records from Royal Belgian Institute of Natural Sciences Bryozoa collection. 443 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 32 records from Ross Coral Mapping Project - NBN South West Pilot Project Case Studies. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 2 records from Fossil Specimens of Komatsu City Museum. 116 records from Programme ACT : Répartition Perdrix rouge 2004 - 2008 Coordonnées GPS Lambert 93. 106 records from Occurrence of mammalia relicts at site Geißenklösterle. 163 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200590. 2349 records from Données naturalistes de Bernard Lalanne-Cassou. 38876 records from Données naturalistes de Xavier CUCHERAT. 24 records from FLOR herbarium - Universidade Federal de Santa Catarina - Herbário Virtual REFLORA. 74 records from Collection of botanical drawings by Georg Schweinfurth at Herbarium Berolinense, Berlin (B). 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 6 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1 records from Collection Quaternary Small Mammals IQW. 3 records from Anguillosyllis (Annelida: Syllidae) from multiple deep-water locations in the northern and southern hemispheres. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 8 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 29480 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 1 records from The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979. 2 records from A molecular phylogeny of Speonemadus Jeannel, 1922 with description of two new species from Morocco (Coleoptera: Leiodidae: Cholevinae: Anemadini). 6873 records from Monitoring of the intertidal biodiversity of rocky beaches with schools in Portugal 2005-2010. 933265 records from SEWBReC Birds (South East Wales). 2 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 33 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 72 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 17 records from Neue Arten der Gattung Atomaria STEPHENS, 1830 aus der Türkei und dem Irak (Coleoptera, Cryptophagidae). 249 records from Collection Echinodermata SMF. 29263 records from MfN - Fossil vertebrates IV. 289 records from Planktic foraminifera abundance of Hole 42-372. 88 records from Foraminifera abundance of sediment core C1966.435. 18 records from Ostracoda abundance of Hole 42-376. 2088 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 3483 records from Arthropod fauna in christmas tree plantations. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 8527826 records from Pl@ntNet automatically identified occurrences. 88 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 112 records from Deanophlebia: A new genus of south-eastern Australian mayflies and subsequent redefinition of the subgenus Nousia (Australonousia) (Ephemeroptera: Leptophlebiidae). 131248 records from Amphibiens et Reptiles de France (Enquête 2). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1588 records from Données naturalistes de Christophe HANOT. 72 records from Données du naturaliste Mael Garrin. 960 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE255. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from Revision of the Recent Alvania scabra (Philippi, 1844) complex (Mollusca, Gastropoda Rissoidae) from the Mediterranean Sea with the description of a new species. 417 records from Programme ACT : Répartition Pie bavarde 2004 - 2008 Coordonnées GPS Lambert 93. 2933 records from Données naturalistes d'Alain BERLY. 135 records from Herps Specimens. 31730 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 183 records from (Table 6) Ostracod assemblages of sediment core 9409. 715 records from Données opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 2 records from Caracterização do grupo Edessa rufomarginata e descrição de sete novas espécies (Heteroptera, Pentatomidae, Edessinae). 2887 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 2996 records from Données naturalistes d'Emmanuel SECHET. 19 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 61810 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 360955 records from Seasearch Marine Surveys in England. 22 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1337. 8 records from A revision of the genus Rhinotorus Förster, 1869 (Hymenoptera, Ichneumonidae, Ctenopelmatinae), with descriptions of three new species and an illustrated identification key. 79 records from BIRDRACE Blinde Hühner. 13046 records from Collection Trichoptera - SMF. 43319 records from Inventaire de la flore des Landes 2016. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Three new species of the family Scathophagidae (Diptera) from the Palaearctic region with a redescription of the male of Amaurosoma longicorne. 14131 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 184 records from Occurrence of mammalia relicts at site Raj Cave. 119 records from Distribution of planktonic foraminifera of sediment core SH1972_16. 14 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 128 records from Arizona State University Hasbrouck Insect Collection. 470 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 187 records from Enquête Laineuse du Prunellier (OPIE). 1253 records from Woodmeadow Invertebrate Survey 2018. 250 records from Collection Strepsiptera SMF. 7 records from A Taxonomic Revision of Nearctic Conostigmus (Hymenoptera: Ceraphronoidea: Megaspilidae). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 156 records from Chironomid remains in the sediment sequence of Site PG1212. 4 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 10 records from Occurrence of mammalia relicts at site Dorog. 4186 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 323 records from Nannofossil abundance of Hole 78-542. 126 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 31391 records from HBRG Fungus, Lichen & Lower Plants Dataset. 62 records from Amtsrain Apolda-Zottelstedt. 72 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 1379 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 128 records from Inventaire des reptiles 2014. 10046 records from Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 583 records from MoJ BioBlitz August 2018. 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 121 records from Owere Fiddel. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 175 records from Ensemble des données. 57 records from Données de la Réserve Naturelle Régionale du Marais de Larchant provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis. 2969 records from Cladocera distribution updates 2014. 255 records from AGIR_Ecologique_2017_12_18. 1 records from Catalogue of the Syrphidae of Egypt (Diptera). 3570 records from Données naturalistes de Nicolas LOEUILLE. 4589 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 1 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 1244 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 23 records from Vom Wert alter Amateursammlungen - vier Spinnenarten neu für die Schweiz in der Sammlung Ketterer. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 17966 records from Insectes Lépidoptères Rhopalocères de France métropolitaine. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 7842 records from Données naturalistes de Cyril EPICOCO. 99 records from Dorfrand Mauderode. 122 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 61 records from Shrews of Poland. 1 records from Platygobiopsis hadiatyae, a new species of deepwater gobiid from Indonesia (Teleostei, Gobiidae, Gobiinae). 1 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 1910 records from Pollen profile from sediment core AV14_K2-3. 122 records from Scottish Beaver Trial incidental species records. 1870 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 4911 records from Vulnerable marine ecosystems in the South Pacific Ocean region. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 82 records from BIRDRACE Die Ziegeneier. 29875 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 1286 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6779 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2934 records from Données d'invertébrés. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 91 records from Lynx 1999 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 1705 records from 16S rDNA metagenomes of Western Balkans glacial lakes sediments. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 4 records from MfN - Micropaleontology. 84 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 55847 records from Données Vigie-Flore. 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59995 records from Données naturalistes de Monsieur François FOURNIER. 4 records from Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea. 1727 records from TWIC Record a Raptor Survey. 74 records from Schulwald Grundschule Brügge. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Sächsische Schweiz (Wehlener Gebiet). 20162 records from Herbarium Horti Botanici Pisani (PI), Sistema Museale di Ateneo, Università di Pisa. 4 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 571 records from Cuxhavener Küstenheiden. 6267 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 1609510 records from Hatikka Observation Database. 6 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 752 records from Données naturalistes de Monsieur JOURDE Rémi. 124 records from Wiesenbiotop am Wasserturm. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 250 records from Inventaire et regroupement de données Natura 2000. 12724 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 638057 records from Données de la flore d’Alsace (SBA). 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 4322 records from Collection Aves (bird skeletons) SMF. 184 records from Synthèse de la Répartition des populations de mouflon méditerranéen en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Korean Insect Database. 738 records from Étude biodiversité toitures végétalisées d'Île-de-France réalisée par Natureparif / ARB. 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2132 records from National Water Vole Database & Mapping Project (Scotland data), 2008. 14 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 2313 records from Données du naturaliste Maillard Bernard provenant de la base de donnée du SINP Île-de-France CETTIA. 37 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1 records from From marine caves to the deep sea, a new look at Caminella (Demospongiae, Geodiidae) in the Atlanto-Mediterranean region. 416 records from Cybelle Méditerranée. Observation nautique avec effort d'observation. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 151 records from BIRDRACE Birding Bentheim. 557 records from Planktic foraminifera counts of sediment core V04-8. 110486 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1177 records from Données opportunistes sur les rhopalocères. 1139 records from SWECO. 4228 records from Données naturalistes de Loïc SALAUN. 8187 records from MfN - Fossil plants (Paleophytic). 8 records from Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia. 911 records from Programme ACT : Répartition Tourterelle turque 2003 - 2007 Coordonnées GPS Lambert 93. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 7319 records from Pseudoscorpion Recording Scheme of the UK. 1560645 records from Flore Franco-Belge. 166 records from Programme ACT : Répartition Grive littorne 2002 - 2006 Coordonnées GPS Lambert 93. 1007 records from Programme ACT : Répartition Pigeon ramier 2011 - 2015 Coordonnées GPS Lambert 93. 7 records from EAC - Herbário Prisco Bezerra. 56 records from Nannofossil abundance of Hole 37-332B. 39 records from Suivi des reptiles en forêt du Madrillet. 2507 records from East Ayrshire Species Database. 100 records from Euroants. 11298 records from Données du naturaliste DEHALLEUX Axel provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions. 110 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 11 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 136 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (3), 2012 - Données faune. 1 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 299 records from Olga Lakela Herbarium, University of Minnesota Duluth. 44 records from Leegmoor (Moormerland/Leer). 6896 records from Collection Crustacea - ZMB. 2 records from Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America. 35 records from Gym Freyung. 6 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 26 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 342 records from Données opportunistes de Mammifères marins SPM de 1997 à 2007 récoltées par le RNE et le Baleineau de SPM de 1997 à 2007. 3 records from Dermaptera in the icipe collection. 50 records from Données naturalistes de Maxime BEAUJEON. 5 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 13 records from Warnowufer Groß Klein. 17 records from Heteroptera - SMNG. 5546 records from Living Collection of the Gothenburg Botanical Garden. 153 records from Données du/de la naturaliste DEHONDT François provenant de la base de donnée du SINP Île-de-France CETTIA. 2575 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 5 records from Revisión taxonómica de Pseudococcus Westwood (Hemiptera: Pseudococcidae) de Centro y Sud América con descripciones de especies nuevas. 387 records from Mollusca collection of National Museum of Nature and Science. 2 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 89 records from Zur Taxonomie und Verbreitung einiger westpaläarktischer Arten der Gattung Planeustomus J V (Coleoptera, Staphylinidae, Oxytelinae). 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 34 records from Integrative revision of the Iberian species of Coscinia Hübner, [1819] sensu lato and Spiris Hübner, [1819], (Lepidoptera: Erebidae, Arctiinae). 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 2 records from Some rare species of cephalobs (Nematoda: Rhabditida: Cephalobidae) from Southern Iberian Peninsula. 959 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 77627 records from Oiseaux nicheurs de France métropolitaine 1985-1989 - nidification certaine. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 150 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto66-74. 39 records from Soolbach-Tal. 238 records from Données du naturaliste Jérôme Hanol. 521 records from Bayerische Donau - Leipheim. 898 records from Collection Agnatha fossil SMF. 480118 records from NMNH Extant Specimen Records. 1 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 384 records from "Schwarzwassertal" bei Pobershau. 107 records from Données de la structure OGE (Office de Génie Ecologique) provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Occurrence of mammalia relicts at site Ejstrup. 1 records from A novel symbiotic relationship between mites and recluse spiders (Sicariidae: Loxosceles), with a description of a new Callidosoma species (Trombidiformes: Erythraeidae). 1170 records from Springtales from lichen communities at Kollåsen in Norway. 1495 records from Données du naturaliste ROUDIE Gilbert provenant de la base de donnée du SINP Île-de-France CETTIA. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 2 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 2 records from Occurrence of mammalia relicts at site Igstadt I. 6191 records from Données naturalistes de Nathalie POT. 308380 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 57 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 53654 records from Biodiversity4all Research-Grade Observations. 13000 records from LPO_PACA_2017_12_18. 5918 records from Macrobenthos and Phytoplankton monitoring in the Belgian coastal zone in the context of the EU Water Framework Directive (WFD). 2 records from Annotated checklist of the fishes of the archipelago of Madeira (NE Atlantic): I-Chondrichthyes. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 4 records from When Citizen Science highlights alien invasive species in France: the case of Indochina mantis, Hierodula patellifera (Insecta, Mantodea, Mantidae). 661 records from Targeting a portion of central European spider diversity for permanent preservation. 46 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 1011 records from Programme ACT : Répartition Merle noir 2006 - 2010 Coordonnées GPS Lambert 93. 39172 records from SEAPOP - Last observation per locality in winter season. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 18 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 361 records from Foreign plant germplasm collections in Ghana. 8 records from New Hemilophini, Aerenicini and Calliini from French Guiana, transference and notes on Hemilophini (Coleoptera, Cerambycidae, Lamiinae). 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 9 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 391 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 464 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 8 records from The InBIO Barcoding Initiative Database: Ypsolopha rhinolophi sp. nov. (Lepidoptera: Ypsolophidae), a new species from Portugal and France unveiled by bats. 91 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 4 records from New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 5471 records from Collection Cnidaria fossil SMF. 459 records from NSG Karwendel. 1036 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 50 records from (Table 1) Time series of ostracod population density off Bokniseck shore ('Hausgarten'), western Baltic Sea. 253 records from Données naturalistes d'Olivier LAURENT. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 6 records from Fiocruz/COLPROT - Coleção de Protozoários. 1 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 2 records from Feather mites of the genera Dubininia and Cacatualges (Acari: Xolalgidae) associated with parrots (Aves: Psittaciformes) of the Old World. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 36 records from Données naturalistes de DUNESME Caroline. 1 records from A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda). 6 records from Wuhle - Brücke / B1. 8 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 2836 records from Marie-Victorin Herbarium (MT) - Bryophytes. 1010 records from Programme ACT : Répartition Merle noir 1999 - 2003 Coordonnées GPS Lambert 93. 1 records from Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 1839 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 243 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 760 records from Programme ACT : Répartition Grive draine 2003 - 2007 Coordonnées GPS Lambert 93. 61 records from Rapportage des données de pêche électriques. 2 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from BIRDRACE Die Wendehälse. 1071 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 2 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 8332 records from Scotland Otter Survey Database. 4 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 21 records from HSU Wildlife Birds. 35 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 298 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 1 records from The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus). 3436 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 160 records from Odonata Central. 161 records from Utah State University, Intermountain Herbarium. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 119 records from Baltic Sea Basin sediments diversity Raw sequence reads. 1660 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 749 records from Mammalogy Collection - Royal Ontario Museum. 223486 records from Phytochorologie des départements français. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 17597 records from Seasearch Marine Surveys in the Isle of Man. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 773 records from CAS Entomology (ENT). 244381 records from Carnet B Lorraine. 9665 records from Naturalis Biodiversity Center (NL) - Pisces. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 12 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 64 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 320 records from Myxomycetes collection of the University of Eastern Finland. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 124 records from Birdrace-LohmannsAdleraugen-Münster. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 6152 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 328027 records from All taxa records for Leicestershire and Rutland. 167 records from Données naturalistes de NOËL Rémi. 542 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 1232 records from GEN_TEREO_2017_12_18. 205 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 202 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 1 records from La Côte oubliée - La Planète Revisitée - Nouvelle-Calédonie 2017. 23 records from Landwehrbach. 21 records from Total foraminifera counts from M35/1_MSN1053. 6 records from Données naturalistes de Mathieu REVEILLAS. 37 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 321 records from Planktic foraminifera counts of sediment core V29-45. 61 records from Alien Species in Poland - Plants. 1733 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 39125 records from Ims fish tag database. 3 records from A new species of Pothea, with new records and taxonomic notes on other species of the genus (Hemiptera: Heteroptera: Reduviidae). 401 records from Données de VINCENT Alexis (SAPROX). 342 records from Nannofossil abundance of Hole 78-543. 39 records from Regenrückhaltebecken Bad Bevensen. 74 records from Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1171 records from Glasgow Museums BRC: Chrysomelidae. 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 2185 records from Inventaire éclair de Natureparif - Année 2015. 543 records from Vascular plants from a study of primary producer traits across an altitudinal gradient in alpine Finse. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 193 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 7249 records from KUBI Herpetology Collection. 49370 records from Tour_du_Valat_2017_12_18. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 2659 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 10 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 1146 records from Bryophytes, fungi and lichens on dead wood. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 2 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 50 records from Artensuche auf den Elbwiesen in Radebeul. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 6 records from The genus Lyroda Say, 1837 in Africa and Arabian Peninsula with description of two new species (Hymenoptera, Crabronidae). 70 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 7568 records from Collection Pisces SMF. 178 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 12 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 2 records from MEXU/Tipos de plantas vasculares. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 23 records from Tümpel Schulbiologiezentrum. 491 records from Naturschutzgebiet Lüneburger Heide. 117 records from Bryozoa of the British Isles. 74 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 430 records from Collection of Heteroptera. 242 records from Landschaftspflegehof (Berlin). 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 10 records from Bachpatenschaft Beeke. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 17 records from A checklist of the Robber Flies (Insecta: Diptera: Asilidae) of Wyoming, USA. 84 records from UAZ Mammals. 3178 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 272 records from Données arachnologiques de LAGARDE Mathieu. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 4647 records from Swedish Malaise Trap Project (SMTP) - Dolichopodidae. 1009 records from Données naturalistes de Daniel PAVON. 70 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 18 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 72 records from Données Réseau National d’Échouages de Saint-Pierre et Miquelon. 693 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 5 records from Discovery of a new species of Trieces (Hymenoptera: Ichneumonidae: Metopiinae) questioning the traditional delimitation between Trieces and Chorinaeus. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 326085 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 45665 records from Botanical Museum, Copenhagen, Mycology Herbarium. 81 records from Seasearch Marine Surveys in the Channel Islands. 98 records from Etude d'impact de la ZAC Bellevue - compléments. 14 records from NCSM Mammalogy Collection. 66 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 124 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 57 records from Abundance of benthos infauna at station GIK23006-3. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 4 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 1 records from VIC - Herbário da Universidade Federal de Viçosa. 30 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 206796 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 51 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 1 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 8107 records from Arctic Ocean Diversity. 110 records from SNH Bat Casework Recording log 2016. 1 records from Biotop Alexander-von-Humboldt-Schule. 115 records from Strathclyde badger sett surveys 1996-2000. 341 records from (Table 7) Planktonic foraminifer abundance of ODP Hole 162-983A. 101 records from RISC Non-Native Species Records for Rhododendron Leafhopper. 414 records from Naturschutzstation Schmidsfelden. 1928 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 80 records from BB-Biodiversität b. 315 records from OUPR - Herbário "Professor José Badini". 237 records from Données du/de la naturaliste Jeliazkov Aliénor provenant de la base de donnée du SINP Île-de-France CETTIA. 194 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 19 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 200 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 1017 records from Programme ACT : Répartition Merle noir 2003 - 2007 Coordonnées GPS Lambert 93. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 39475 records from Vascular plant diversity in forests. 4 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 123546 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 11091 records from Caddisfly (Trichoptera) records from Britain and Ireland, via iRecord. 975 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 1070 records from KUBI Mammalogy Collection. 3 records from New species of Thelepodidae (Terebelliformia, Polychaeta) from Taiwan. 92 records from Nottekanal, Klasse 7 - 10. 245 records from Nannofossil abundance of Hole 37-333. 2740 records from RNF - Données du Parc Naturel Régional de la Forêt d'Orient. 80 records from Distribution of introduced plants in Ukraine. 4733 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 17073 records from données aranéologiques de CORNIC Jean-François. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 8200 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 114 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 74 records from Données espèces - Expertise IPE 69. 2 records from Description of a new species of Pagurus Fabricius, 1775 (Crustacea: Paguroidea: Paguridae) from the Pacific coast of Costa Rica, Central America, with notes on Pagurus albus (Benedict, 1892). 107 records from 1st Austrian Birdrace (Wien). 1 records from A review of the gall midges (Diptera: Cecidomyiidae) of Indonesia: taxonomy, biology and adult key to genera. 102 records from BIRDRACE HGON Kelkheim-Rumpfteam. 4713 records from Planktonic foraminifera in ODP Hole 160-963A. 463 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 6622 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 121 records from Inventaire Faune. 124 records from Données naturalistes de Nicolas GALAND. 198231 records from MICROBIS database. 78246 records from Données de l'AFB acquises selon le protocole de pêche partielle par points. 123 records from Birdrace-Professorenteam-Münster. 33 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 485667 records from Swiss National Grasshoppers Databank. 64 records from Planktic foraminifera counts at CTD station PS55/083-1. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 30091 records from BIOWIDE eDNA Fungi dataset. 79 records from A review of the spider genus Porrhomma (Araneae, Linyphiidae). 133 records from Pollen profile II/B at Krumbach, Germany. 3722 records from Rutgers University, Chrysler Herbarium. 7 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 19005 records from Weevil and Bark Beetle records via iRecord. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 2548 records from Distribution of ostracoda in the lower Cretaceous succession of ODP Hole 80-549 (Figure 3). 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 30 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 38 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 16811 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 4 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 45833 records from The national database for marine data (MADS). 157 records from Programme ACT : Répartition Pigeon colombin 2008 - 2012 Coordonnées GPS Lambert 93. 3679 records from Röntgenarchiv Wilhelm Stürmer - SMF. 10 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 7407 records from Dipterists Forum: Field Week 2018 (Stoke). 15491 records from Waterway Survey. 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 1267 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 31 records from Nationalpark Harz Schul-AG Braunlage. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 14570 records from Skandobs. 1072 records from Walldorf-Wiesloch: "Natur über den Gleisen". 7917 records from Diversity of archaeal and bacterial 16S rRNA gene in marine sediment in Aarhus Bay. 38 records from Was lebt in der Brutzwiese?. 636 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 17 records from Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China. 15 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 905 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 86 records from Données naturalistes de Pierre-Alexis RAULT. 109 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 212 records from Am Moosangerweg. 2301 records from Dark ocean microbial diversity. 582 records from Bioblitz 2013 Copenhagen Denmark. 1 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 7 records from PRECIS (KwaZulu-Natal Herbarium). 5 records from Iberolygus n. gen., from the Iberian Peninsula (Hemiptera: Cimicomorpha: Miridae: Mirinae), with a new generic combination for Apolygus rubrostriatus (Wagner, 1971). 40 records from Support for the underrepresented sex: new descriptions of scutacarid males (Acari, Heterostigmatina). 17 records from Kohlbach (Sulzfeld). 134 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 26 records from Fossil (NSMK-FO). 448 records from SOUTHERN OCEAN ISOPODA. 2 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 52428 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 3 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 54353 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondées sur des photographies. 7319 records from Fish damage at pump stations. 389 records from Données espèces - Expertise IQE 89. 1000 records from Hoverflies (Syrphidae) of Ireland. 1 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 68 records from Occurrence of mammalia relicts at site Ettingen. 28 records from Total foraminifera counts from M35/1_MSN1058. 9 records from South Caribbean Diversity. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 719 records from Programme ACT : Répartition Alouette des champs 2012 - 2016 Coordonnées GPS Lambert 93. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 1228 records from Suivis télémétriques des Otaries des Kerguelen par le Centre d'Etudes Biologiques de Chizé. 21839 records from International Fossil Shell Museum (NL) - Mollusca Collection. 2 records from Livingstone Museum Bat Collection. 486 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 166 records from Redshank nesting on saltmarshes in Britain. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 198 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 2 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 2 records from Traumatomutilla André miscellanea: Revision of the bellica, bifurca, diabolica, and vitelligera species groups, and a new group for the new species T. pilkingtoni Bartholomay and Williams (Hymenoptera: Mutillidae: Sphaeropthalminae: Dasymutillini). 45 records from Gastropods from the Cretaceous-Palaeogene boundary in Denmark. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 14897 records from Rådgivende Biologer. 11249 records from Heteroptera collections of SW Finland. 68 records from Abundance of planktic foraminifera at CTD station PS55/025. 120 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 622 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 689 records from Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 3558 records from Regroupement de données Odonates. 97 records from POPA- Fisheries Observer Program of the Azores: Sea turtle sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 47 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 735 records from EDP Foz-Tua: Vascular Flora – Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 105 records from Lynx 2015 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 219 records from CUMV Fish Collection. 6907 records from MUST, Insecta. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 1027799 records from Données ONF faune-flore-fonge. 1602 records from Collection entomologique Pierre Lachiver. 10 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 1463 records from Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 16 records from Occurrence of mammalia relicts at site Trebacki krs. 4123 records from University of Tennessee Fungal Herbarium. 13780 records from University of Michigan Museum of Zoology, Division of Mollusks. 1 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 32 records from Site Condition Monitoring of the downy willow Salix lapponum component of the Vascular Plant Assemblage interest of Skinsdale Peatlands SSSI, 2016. 2 records from Setaphyes elenae sp. nov., a new species of mud dragon (Kinorhyncha: Allomalorhagida) from Skagerrak (north-eastern Atlantic Ocean). 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 29912 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 1307 records from Données opportunistes. 258148 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 636 records from Type Specimen Database of Museum and Institute of Zoology PAS. 62156 records from DASSH Data Archive Centre Academic Surveys. 3784 records from Herbier de Wallis et Futuna. 9 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Muséum national d’Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 11 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 222 records from Occurrence of mammalia relicts at site Roc de Combe. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 15028 records from University of Florida Invertebrate Paleontology. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 2 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 94 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 11 records from Données naturalistes de Thibault RAMAGE. 43 records from Vogelstimmenführung durch den Tiergarten. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 16738 records from Inventaire des Ephémères de métropole (Opie). 308 records from Echinodermata of Montenegro (South Adriatic). 122 records from Lynx 2007 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 195 records from Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 4688 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 22 records from Propriété régionale du Moulin des Marais - Inventaire naturaliste 2015. 5 records from University of Kentucky Insect Collection. 51903 records from Atlas des Orthoptères et Mantides de France métropolitaine. 64 records from Données du/de la naturaliste Bourdin Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 169 records from UAM Bird Collection (Arctos). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 391 records from GEOECOLINK_2017_12_18. 96 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 2 records from UTEP Herpetology Osteology (Arctos). 2072 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 135996 records from The Scottish Squirrel Database. 1 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 96 records from BIRDRACE OAG Neuwerk. 2 records from Planktic foraminifera counts of multinet PS2616-5. 2 records from New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece. 591 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 120 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 408 records from Données naturalistes de Jean-Michel LEMAIRE. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 39624 records from Fife Nature Records Centre combined dataset. 9 records from Occurrence of mammalia relicts at site Dolni Vestonice. 2 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 261 records from Programme ACT : Répartition Alouette lulu 2007 - 2011 Coordonnées GPS Lambert 93. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 1 records from Review of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha Cicadellidae: Eurymelinae: Macropsini) of Southeastern Kazakhstan with description of new species. 126 records from Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 1843 records from Invasive Alien Species in Denmark. 52 records from Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Motzener Tonsee. 272 records from BIRDRACE Niederlausitz-Team. 3 records from New European records of Ditomyia macroptera Winnertz (Diptera: Ditomyiidae) with notes on its distribution. 4077 records from SOPTOM_2017_12_18. 941 records from Programme ACT : Répartition Pigeon ramier 1996 - 2000 Coordonnées GPS Lambert 93. 95 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 17 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 11824 records from Collection Herpetology SMF. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 265 records from Survey of giant hogweed, Japanese knotweed and Himalayan balsam on 5 major Lothian rivers, 2003/04. 1201 records from Waarneming.nl (NL) - Great Grey Shrike Count 2012-2013. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from Données naturalistes de PICHARD Olivier. 178 records from Corn bunting surveys on the Western Isles. 2579 records from Archives of the Arctic Seas Zooplankton. 375 records from CG04_2017_12_18. 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 719 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 10747 records from The Fish Collection. 181 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 115 records from Collection Ephemeroptera - SMF. 530 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 20 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 10313 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 1978 records from Invasive Non-Native Species. 4 records from A new Mediterranean species of Dolistenus (Diplopoda, Platydesmida, Andrognathidae), with an updated key for the genus and the first contribution for a barcode database of European Platydesmida. 818 records from Denver Museum of Nature & Science - Entomology. 46 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16506 records from Database for alien invasive plants occurrences in Germany. 181 records from Life cycle and production of Canuella perplexa (Copepoda, Harpacticoida) in the Sluice dock Oostende between 1976-1978. 8 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 3 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 85 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 38512 records from Herbier de Strasbourg. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 36 records from Selz (Ingelheim am Rhein). 150 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 83 records from European bison in Białowieża Primary Forest. 102 records from A Lichen Survey of the Ben Nevis Plateau. 5702 records from pins. 1 records from Three new species and a new record of tenuipalpid mites (Acari: Tenuipalpidae) from Hungary. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 2256 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 52 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 9990 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 345 records from Données naturalistes de Laurent PONCET. 2456 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1023 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 2 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 149 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 170 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 2338 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 3188 records from Butterfly_conservation_2017_12_18. 16458 records from Inventaires faune. 14 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137476 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 53 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 3 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 28637 records from Données bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 17 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 99 records from Düne am Ulvenberg (Darmstadt). 22 records from Données naturalistes d'Emilie WEBER. 27660 records from Mammals housed at MHNG, Geneva. 14471 records from Löydös Open Invasive Alien Species Observations. 2352 records from Mammal osteology MZS. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 10 records from Sediment properties of core PLG95B_01BOXG. 1562 records from Swiss Psyllid (Hemiptera) Collections - Basel. 155 records from Données du/de la naturaliste VAN DEN BRINK Sylvie provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 982 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 257 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 4 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 4378 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 425 records from données bibliographiques diverses (non araignées). 22 records from UNM Earth Sciences Collection (Arctos). 1016 records from Programme ACT : Répartition Merle noir 2002 - 2006 Coordonnées GPS Lambert 93. 10229 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 2 records from New and interesting species of the generaGalumna andPergalumna (Acari, Oribatida, Galumnidae) from the Montagne d’Ambre National Park, Madagascar. 82 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 13 records from Données naturalistes de BRULE Hervé. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 135 records from Boreonemoral regnskog på østsiden av Lygrespollen. 26 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 85 records from Données espèces - Expertise IPE 123. 50 records from Beetles on polypores at 4 sites in Norway. 903 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 29 records from Collection Crustacea - ZSRO. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 2 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 157 records from BIRDRACE Rheinische Wasserrallen. 91 records from Loup 2004 présence régulière communale (réseau Loup-Lynx ONCFS). 4579 records from Données naturalistes de David HAPPE. 493 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 5453 records from Données coléoptères de l'Association des Entomologistes de Picardie. 4 records from A revision of Japanese Torymus Dalman (Hymenoptera: Torymidae). 13384 records from Coleoptera collection of Uunio Saalas. 7 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 15452 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 487 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 514 records from EDP Foz Tua: Bat Roosts - Ecological & Compensatory Measures Monitoring Programs [2011-2017]. 1359 records from GEO Biodiversity Day. 15 records from Inventaire et suivi de la Cistude d’Europe sur le site Natura 2000 ‘Zones humides de Moliets, La Prade et Moisans’ (FR7200718). 13 records from Colección de Zoología Invertebrados - Helmintología. 458 records from IASTracker. Invasive Alien Species database. 8 records from Lynx 1988 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 89762 records from Ornitho.eus. 64 records from Planktic foraminifera assemblage in sediment core SU90-I06. 1361 records from The Bergius Herbarium. 9479 records from Fishes of INEP and NFH collections. 210734 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 62 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 75 records from Naturpark Kottenforst-Ville 19.6.09. 2 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 68 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 73 records from Swedish Malaise Trap Project (SMTP) - small Sciaroidea families. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 47 records from Sea lamprey distribution and abundance in the River Spey: phases II and III, 2001/2002. 1068 records from UCBG TAPIR Provider. 818 records from The Golden wasps collection (Chrysididae) at the Staatliches Museum für Naturkunde Stuttgart. 13 records from Montana State University - Billings. 333 records from renaturierter Main (Kemmern bei Bamberg). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 479 records from Geochemistry and sedimentology on core POS200/10_28-1. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 3 records from Palaeopsylla (Palaeopsylla) aysenurae n. sp., a new ctenophthalmid flea (Siphonaptera: Ctenophthalmidae) from Turkey. 133550 records from Observations Regelink Ecology and Landscape. 240665 records from Oskarshamn herbarium (OHN). 571 records from Synthèse de la Répartition des populations de chamois en 2006 (réseau Ongulés sauvages ONCFS-FNC-FDC). 9446 records from Batsites inventory for England (1949-2011). 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 1 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 59005 records from Isopoda (Interim dataset). 190 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 89 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 250336 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 1 records from Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae). 474 records from Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 3334 records from Algae collection, Oslo (O) UiO. 402 records from Données du/de la naturaliste delzons olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 9101 records from Données naturalistes de Jean-Paul LECHAPT. 1 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 40 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 2 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 967 records from Inventaire des Odonates. 129 records from Global Distribution and Diversity of Solenidae Species. 36 records from BIOMEO_2017_12_18. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1828 records from Inventaire de la flore de la Communauté Urbaine de Bordeaux 2009. 1 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 2 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 3 records from Lance lacewings of the world (Neuroptera: Archeosmylidae, Osmylidae, Saucrosmylidae): review of living and fossil genera. 76 records from Inventaire hivernal des nids de frelon asiatique. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 18 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 4023 records from Bell Museum fungi. 165 records from EDP Foz-Tua: Terrestrial Birds (occasional observations)- Complementary Studies [2009-10]. 181 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 6 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 98 records from Occurrence of mammalia relicts at site Koziarna Cave. 102 records from BIRDRACE Westfälische Nachtigallen. 809 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 114246 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 445 records from Collection ornithologique A. Maës. 1 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 2 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12 records from Occurrences de Bouquetin ibérique (Capra pyrenaica) collectées par le PNP et le PNRPA. 543 records from (Table 8) Planktonic foraminifer abundance of ODP Site 162-984. 46 records from Aktion Wiese und Wegrain Gitzenheide. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 41 records from Örtzemündung (Stedden). 159 records from Invertebrates compiled by W.Block. 71 records from Bolzplatz. 673 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 3 records from Whip spiders (Amblypygi, Arachnida) of the Western Palaearctic—a review. 202 records from Données naturalistes de Monsieur VILAIN Frederic. 15 records from Descriptions of two new genera of Maruinini (Diptera, Psychodidae, Psychodinae) from the Mitaraka range of French Guiana. 12 records from Sternaspis chilensis n. sp., a new species from austral Chilean channels and fjords (Annelida, Sternaspidae). 60221 records from National Stag Beetle Surveys (Great Stag Hunts). 1734 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 3032 records from Fishes in MZNA-VERT: interactions between signal crayfish and fish communities. PhD project, Iván Vedia. 177 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 306-U1313. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 218 records from Étude vallons froid - Parc naturel régional de Lorraine. 1694 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 319 records from Données naturalistes de Monsieur LEFEBVRE François. 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 47 records from Occurrence of mammalia relicts at site Sütto_6. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB05 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 3298 records from Herbarium of Taiwan Forestry Research Institute. 17 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 23 records from Ackerrain Plönhagen. 1004 records from Données odonates. 26828 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 47 records from The grasshoppers (Orthoptera, Acridomorpha) from the Mitaraka Mountain Range, French Guiana. 313 records from BIRDRACE Gätkes Erben. 3249 records from Benthos counted on dredged samples during Valdivia cruise VA53. 163 records from Marine sediment metagenome ICM_CFU. 4 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 3028 records from My naturesounds - nature observations with sound recordings. 547 records from arthropods on Plantago lanceolata. 166465 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 6786 records from Invertebrate collection of University of Oulu Zoological Museum. 4644 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 5 records from University of New Mexico Herbarium. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 1387 records from Phytoplankton abundance during ARGOS cruise Argos91/5. 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Notes on taxonomy and distribution of some Palaearctic Ancylosis Zeller, 1839 (Lepidoptera: Pyralidae: Phycitinae). 1040 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 2225 records from Données naturalistes d'Anaïs MAS. 14 records from Occurrence of mammalia relicts at site Bedburg-Königshoven. 117 records from Wassermann. 91 records from Données de la naturaliste Estelle Duchemann. 1 records from Cryptic species in the nuisance midge Polypedilum nubifer (Skuse) (Diptera: Chironomidae) and the status of Tripedilum Kieffer. 7368 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34045 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 177 records from Suivi temporel des Rhopalocères 2016. 36 records from Ours 2013 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 1895 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 29 records from Lynx 1993 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 14 records from Ibaraki Nature Museum, Mollusk collection. 85 records from New findings of the butterfly Phengaris teleius at the border between Hungary and Serbia (Lepidoptera: Lycaenidae). 1 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 2844793 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 3 records from FFR Hausen. 14 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 88 records from NCSM Herpetology Collection. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 64004 records from Environment Agency England and Wales (2007) freshwater invertebrate species (single species families). 18 records from ALTERECO_2017_12_18. 1 records from HURB - Herbário do Recôncavo da Bahia. 6640 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 527736 records from BioFokus. 10941 records from Données lichens de l'ATBI Parc National du Mercantour / Parco Naturale Alpi Marittime (AFL). 13225 records from Anymals+plants - Citizen Science Data. 27167 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 859 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 16128 records from données araneologiques de TOURNEUR Jérôme et CPIE Loire-Anjou. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 639 records from Programme ACT : Répartition Faisan commun 2006 - 2010 Coordonnées GPS Lambert 93. 1 records from Orthotrichum dentatum T. Kiebacher & Lüth sp. nov. (Orthotrichaceae). 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 108 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 498 records from 13C methanol SIP (WCO station L4). 7895 records from Tetraonid line transect surveys from Norway: Data from Finnmarkseiendommen (FeFo). 71 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 144 records from Fossil (WSHN-FO). 6 records from Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico. 1827 records from Données naturalistes de Pascal ROUSSE. 3224 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 7248 records from DBRC Hemiptera species records 1969 to 2015. 38 records from BB-Biodiversität a. 8 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 3546 records from Dorset SW Pilot species dataset. 1918 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 18 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 154 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 13845 records from Cumbria Non Native Invasive Species. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune écrasée. 32 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 459 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 22 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 73 records from Mollusc collection Natuurmuseum Brabant, Tilburg. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 123 records from DAR AVH data. 170543 records from England Non Native Species records 1965 to 2017. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 313 records from DBL_Life. 1178 records from Océanopolis mammifères marins en Bretagne 1993-2015. 29732 records from BLS Rare and Threatened Lichen Records: England. 145 records from Gronau - auf der Suche nach dem Neunauge. 1120 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 19535 records from Eden Arthropod Azores Database. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 2171 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 1879 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 122 records from BIOTOPE_2017_12_18. 108 records from BIRDRACE Diesmal sehen wir mehr. 1420 records from Weevils of Poland. 3 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 2 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 675 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 14257 records from Inventaire de la flore du PNRLG 2016 (Gironde). 287 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 1 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 3 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 37 records from uncultured bacterium Targeted Locus (Loci). 5 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 234 records from Pollen analysis of sediment profile BLA00 from Blankensee. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 7 records from Données naturalistes d'Olivier VILLEPOUX. 6 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 17 records from NCSM Non-molluscan Invertebrates Collection. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 301 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 691 records from The AAU Herbarium Database. 323 records from DSMZ Collection of Plant Viruses. 3 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 5 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Newly reported genus Batracomorphus Lewis (Hemiptera: Cicadellidae: Iassinae) from Pakistan with description of a new species. 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 724 records from Heritage Trees of Ireland. 32 records from Craigellachie NNR invertebrate records compiled from SNH files. 240 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 210 records from Collection Polychaeta - ZSRO. 15601 records from imr_mareano_rpsledge. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 88159 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 245 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 8 records from RISC Non-Native Species Records for Zebra Mussel. 46 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 22 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 100 records from Données d'observation d'écrevisses exotiques envahissantes en Haut de France et Normandie sur la période 2014 à 2018. 234 records from Freshwater fish records via iRecord - additional species. 20 records from Abundance of benthos infauna at station GIK23055-1. 26 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 22575 records from Living plant collection of Meise Botanic Garden. 6 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 378 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 5644 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 418 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 2 records from Kirchenforst. 4777 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 9658 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 10 records from Nannofossil abundance of Hole 15-146A. 2 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 2 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 240 records from UWFC Ichthyology Collection. 813 records from Programme ACT : Répartition Tourterelle des bois 1996 - 2000 Coordonnées GPS Lambert 93. 432 records from Auburn University Museum of Natural History Invertebrates. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 1 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 3575 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 6 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 26 records from Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species. 1296 records from Comptage Wetlands en Essonne. 34 records from Planktic foraminifera counts of sediment core V27-47. 1 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 418 records from Marine algal (seaweed) flora of Terceira Island, Azores. 23 records from AlgaTerraMovies. 228 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 829 records from Programme ACT : Répartition Geai des chênes 2007 - 2011 Coordonnées GPS Lambert 93. 27 records from synthese_Protistdiversity_KG. 127 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 875 records from Bird collection Natuurmuseum Brabant, Tilburg. 4 records from of patch-nosed snake (Colubridae: Salvadora Baird and Girard, 1853) from Oaxaca, Mexico. 46217 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 77 records from Benthic foraminifera abundance of Hole 42-372. 469908 records from Natural England Marine Monitoring surveys. 3 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 357 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 19899 records from Ground Beetle Recording Scheme - data verified via iRecord. 2 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 2520 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 2013 records from Coleoptera Collection. 3 records from Extended diagnosis of the type species of Pseudogonatodes Ruthven 1915 (Gekkota Sphaerodactylidae). 7 records from Inventaire et suivi Ecrevisses. 415 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 23 records from Ours 2016 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 1 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 1 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 16 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 24642 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 213 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 5 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 1550 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 590353 records from Welsh Invertebrate Database (WID). 67 records from An annotated catalogue of Elachistinae of the World (Lepidoptera: Gelechioidea: Elachistidae). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 4104 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 4081 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 8 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 39446 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 26 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1116 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 1 records from Toward a revision of the bamboo corals: Part 1, species in the Muricellisidinae (Octocorallia: Isididae). 711 records from Programme ACT : Répartition Alouette des champs 2009 - 2013 Coordonnées GPS Lambert 93. 53961 records from Long-Term Monitoring Network Vegetation Quadrats. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 1075 records from Inventaire et suivi Rhopalocères. 15338 records from Données naturalistes de Pierre FRAPA. 202 records from Collection Crustacea ZMG. 83 records from Naturpark Kottenforst-Ville 16.6.09. 1 records from Spirlins of the southern Black Sea basin, with the description of a new species (Teleostei: Leuciscidae). 8286 records from Araneae Collection. 1 records from Description of two females of Leptagrion Selys (Odonata: Coenagrionidae). 17 records from Updated checklist of French Guianan Asilidae (Diptera) with a focus on the Mitaraka expedition. 5 records from Inventaire des sangsues - détermination des échantillons de l'enquête participative - Subvention UMS Patrinat. 661 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 118 records from Natur aus zweiter Hand am Muldestausee. 367 records from Données naturalistes de Christophe HERVE. 169 records from Analysis of the macrobenthic community near Nieuwpoort (1970-1971). 191 records from Fauna inventories from the intertidal zone in Wimereux, France. 471508 records from SER Species-based Surveys. 175805 records from River Macrophytes Database. 163054 records from NINA insect database. 1140 records from Macromycetes in Portugal Update. 5972 records from Inventaire de la flore des pelouses littorales de l'estuaire de la Gironde en Charente-Maritime 2012. 80 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3999 records from PNR_Alpilles_2017_12_18. 48710 records from Lichen herbarium TRH, NTNU University Museum. 93 records from Höltigbaum. 247 records from Données du/de la naturaliste DURAND Bruno provenant de la base de donnée du SINP Île-de-France CETTIA. 428 records from Swedish Malaise Trap Project (SMTP) - Auchenorrhyncha excl Delphacidae. 17 records from Five new species of Enchytraeidae (Annelida: Clitellata) from Mediterranean woodlands of Italy and reaffirmed validity of Achaeta etrusca, Fridericia bulbosa and F. miraflores. 565 records from Synthèse de la Répartition des populations de daim en 2013 (réseau Ongulés sauvages ONCFS-FNC-FDC). 99 records from BIRDRACE TEAM BO-BACHTER. 56 records from Zitadelle Berlin-Spandau (7b). 266 records from Inventaire forestier en forêt tropicale primaire de Guadeloupe. 82 records from General Biodiversity Records from Ireland. 10205 records from Collection entomologique Barthélémy. 459 records from Enquête Abondance Grande faune forestière de Guyane (ONCFS). 1302 records from Winter colonies of Kuhl's bat (Pipistrellus kuhlii subsp. lepidus Blyth, 1845) in Ukraine, 2013-2020. 68 records from Sandhofen. 346830 records from Flore d'Ille-et-Vilaine. 967 records from Relevé flore exotique isolée de La Réunion. 6512 records from ULg_Hexapoda. 6084 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 175 records from Neißetal. 8913 records from ZFMK Orthopteroidea collection. 89 records from Données espèces - Expertise IPE 83. 101 records from Données de présence collectées sur les odonates. 8339 records from Projet SYRFID 2 (données bibliographiques sur les Syrphes de France). 3 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 1 records from The identity of Equatobursa, with proposal of new genus and species level synonymies (Hemiptera: Heteroptera: Heterogastridae). 1175 records from Données du/de la naturaliste SALMON Anne-Sophie provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Entomobrya (Collembola, Entomobryidae) for the Canary Islands. 31 records from Review of the genus Singilis Rambur, 1837 of North Africa and Iberian Peninsula (Coleoptera: Carabidae: Lebiini). 4 records from Microplankton abundance at bottle station SEPT-1999-K9. 2 records from Loxosomella decorata n. sp., a new solitary entoproct from San Juan Island, WA, USA. 34 records from A taxonomic monograph of the genus Solariola Flach, 1908 (Coleoptera: Curculionidae: Entiminae). 7 records from Two new species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with a new record from Australia. 4 records from A new species of arboreal microteiid lizard of the genus Euspondylus (Gymnophtalmidae: Cercosaurinae) from the Andean slopes of central Peru with comments on Peruvian Euspondylus. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 2553 records from Données de la structure MNHN provenant de la base de donnée du SINP Île-de-France CETTIA. 83 records from The genus Haplodrassus Chamberlin, 1922 in the Mediterranean and the Maghreb in particular (Araneae: Gnaphosidae). 1 records from The oldest fossil of the family Issidae (Hemiptera, Fulgoromorpha) from the Paleocene of Menat (France). 39 records from Ours 2012 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 7 records from Provisional checklist of the Tettigonioidea (Insecta: Orthoptera) from São Tomé & Príncipe with taxonomic remarks, bioacoustical data and the description of new taxa. 207 records from Foraminifera abundance of sediment core MD81-LC03. 201 records from Synthèse de la Répartition des populations de mouflon méditerranéen en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC). 595 records from Fish data of the Belgian River Meuse from 1989 to 2012. 11 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 21 records from Riedkanal Bötzingen. 10 records from Occurrence of mammalia relicts at site Ochtendung. 136 records from Données de la structure ACOREP provenant de la base de donnée du SINP Île-de-France CETTIA. 136 records from Size of planktic foraminifera at CTD station PS55/030. 817 records from Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 1229 records from MEXU/Colección de Briofitas. 236 records from City of Edinburgh Natural Heritage Service - General Public Records.. 953 records from Pollen profile Märchenwald B, Harz, Germany. 243 records from Thistles species and abundance. 2126 records from The Vascular Plants Collection of the University of Goettingen. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 717 records from Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 1 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 17 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 814 records from flower availability 2008 Hainich. 58 records from Type locality records of Polycystididae species in the world. 202053 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1 records from Andes to Amazon Biodiversity Program. 7 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1122 records from Données naturalistes de Stéphane ORIO. 63 records from Collection Echinodermata - ZMB. 60 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 3914 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 2869 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 1066 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Vestland, Troms and Finnmark, Norway (2019). 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 2237 records from Jardín Botánico Atlántico, Gijón: JBAG. 539 records from étude entomologique de la ZSC du Bois de Vaires. 3990 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 587 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 13 records from FBIP: SeaKeys - iziko_cartilaginous_fish. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 105 records from Fish Fauna of Berlin. 4696 records from Kherson State University herbarium (KHER), Department of Botany. 29 records from Total foraminifera counts of trap L3_92_45. 4 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 1945 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 751 records from Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 2573318 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 479 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 161 records from MfN - Fossil invertebrates IIa. 959 records from Département_du_Var_2017_12_18. 7 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 47 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 48 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 2256 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 39 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 1037 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 1 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 63 records from Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 272 records from Annales de la Société entomologique de France [1832- ]. 564 records from Hymenoptera specimen database of Kyushu University. 724998 records from Finnish Floristic Database (Literature Sources). 402 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 2 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 3245501 records from iNaturalist Research-grade Observations. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 37 records from Bohemannia auriciliella (Nepticulidae) specimen data. 1365 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 64 records from Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 1 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 1 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 24 records from Abundance of benthos infauna at station PS1240-1. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 80 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 694 records from données arachnologiques de CARR David. 47 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 5401 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 188 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 6 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 31 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 261 records from Données espèces -expertise IQE 3. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 20 records from Collection Berlie. 360 records from Données du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 61366 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 71 records from JCT AVH data. 2555 records from University of Tennessee Bryophyte Herbarium. 174 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2665 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 176 records from Paleobotany Specimens. 16924 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6541 records from Likona Invertebrates. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 2 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 338 records from EDP Foz-Tua: Fishes – Ecological Monitoring Program [2011-2017]. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Données naturalistes de Arnoul MATEO. 18 records from Occurrence of mammalia relicts at site Ochoz Cave. 2177 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE241. 3 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 1439 records from Coleção Entomológica do Museu Nacional / UFRJ. 4344 records from KUBI Paleobotany Collection. 39 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 52 records from Distribution of Aureoboletus projectellus in Europe. 11163 records from Programme FLASH : Répartition Pigeon ramier 2012 - 2016 Coordonnées GPS Lambert 93. 16 records from Wild boar culled on the National Forest Estate Scotland 2018-19. 2266 records from Canadian Museum of Nature Herbarium. 1522157 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 206 records from Nannofossil abundance of Hole 78-542A. 899 rec
Keywords: GBIF; biodiversity; species occurrences